Pelatihan Pembuatan Eco Enzym Kepada Masyarakat RT 27 dan 35 Desa Muang Ilir Samarinda - Nova Hariani; Rizky Rahman; Aura Nur Kholifah; Muhammad Gunawan; Pamela (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
Eco enzyme training for locals, especially for housewives at RT. 13, Muang Ilir village, Lempake, in Samarinda. The training is about producing and obtaining benefits of environmentally friendly enzyme products, a program which designed to introduce participant on basic and practice of eco enzyme for producing and obtaining benefits from it. Eco enzyme is fluid resulting from fermentation of organic material, like leftovers (fruits and fresh vegetables) which is household waste by adding organic sugar into water with the help of microorganism. The fluid has numerous benefits for the environment and various applications in the household, agriculture, even in industrial sector. Socialization and training aim to provide information and educate people to care about waste and get benefits from it. Socialization was done by talk followed by practice for eco enzyme producing. After training, satisfaction result show the average value was very satisfactory (scored 5 of 94% participants) and satisfactory (scored 4 of 6% participants). Overall, all participants were very enthusiastic towards knowledge about eco enzyme, thus they can practice it at homes.Â Moreover, the locals hope a further collaboration in terms of sharing knowledge from university with Biology Department, FMIPA,and UKM Lesehan Cendikia Mulawarman University, especially for the locals from RT.13, Muang Ilir village, Lempake, in Samarinda.Â